Enhanced recycled aggregate cement concrete based on long-acting carbon sequestration and preparation method thereof
By introducing activated carbon capture agent and microencapsulated materials into the regenerated aggregate cement concrete, combined with carbon capture active agent, long-term carbon storage and strength improvement are achieved, and the problems of excessive carbon dioxide emissions and insufficient strength in the prior art are solved.
Patent Information
- Application Number
- CN202510004886.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The prior art cannot achieve long-term carbon sequestration in the production process of recycled aggregate cement concrete, resulting in excessive carbon dioxide emissions and insufficient strength and durability of recycled aggregates, which limits its application in road engineering.
A reinforced recycled aggregate cement concrete based on long-term carbon sequestration is adopted. Dynamic carbon capture and long-term carbon sequestration are achieved by introducing recycled aggregate, activated carbon capture agent and microencapsulated carbon sequestration into the material, combining carbon capture active agent and microencapsulated carbon sequestration materials.
The recycled aggregate cement concrete has been continuously absorbed in carbon dioxide during its service period and stored for a long time, which has significantly improved the strength and durability of the material, and solved the problems of low strength and poor interface bonding performance of traditional recycled aggregates.
Smart Images

Figure CN119774951A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of road engineering materials and environmental protection, and specifically relates to an enhanced recycled aggregate cement concrete based on long-term carbon sequestration and a preparation method thereof. Background Art
[0002] With the rapid advancement of industrialization and urbanization, the construction industry has developed rapidly, and new infrastructure projects can be seen everywhere. A large number of existing buildings have reached their service life or cannot meet the use requirements and have been demolished. This phenomenon will not only cause a huge waste of construction resources, but also lead to the increasingly serious problem of construction waste siege. If a large amount of construction waste cannot be effectively utilized or properly disposed of, it will cause a serious waste of resources and will also aggravate the serious damage to the natural environment. Therefore, achieving effective recycling and reuse of construction waste is an important research direction in the current field of environmental protection.
[0003] As an important part of my country's infrastructure construction, road engineering is large in scale and consumes a large amount of natural sand and gravel materials every year. At the same time, roads can be divided into multiple grades according to functional differences and multiple levels according to structural layer differences, which has the possibility of absorbing a large amount of recycled aggregates with different physical properties. However, the poor strength and durability of recycled aggregates will limit their use in actual road engineering.
[0004] Recycled aggregates can be used to produce cement concrete, but a large amount of carbon dioxide will be emitted during the recycling, crushing or processing of recycled aggregates and during the production of recycled aggregate cement concrete, which will cause serious pollution to the environment. In order to reduce carbon emissions and improve the sustainable development of building materials, green and environmentally friendly recycled aggregate cement concrete technology has become a research hotspot in the industry.
[0005] In the production and preparation process of recycled aggregate cement concrete, the existing technology mainly injects industrially prepared high-concentration carbon dioxide into cement test blocks to seal carbon dioxide in the form of carbonate to improve the strength of recycled aggregates. However, the amount of carbon dioxide absorbed by recycled aggregates is limited, which in turn leads to the emission of a large amount of carbon dioxide again, and the cost is high; in addition, high-concentration carbon dioxide cannot be continuously absorbed into cement test blocks, and the effect of long-term carbon sequestration cannot be achieved. Therefore, it is urgent to develop an enhanced recycled aggregate cement concrete based on long-term carbon sequestration and a preparation method to achieve the effect of continuously absorbing and sealing carbon dioxide and significantly improving the strength and durability of recycled aggregates.
[0006] The invention patent with application publication number CN117536045A discloses a carbon sequestration all-solid waste assembled permeable pavement system, including a carbon sequestration solidified mud slag base, an assembled interlocking permeable carbon sequestration recycled concrete base, a carbon sequestration recycled fine aggregate leveling layer and an assembled interlocking permeable carbon sequestration recycled brick pavement arranged in sequence from bottom to top, and also includes a drainage pipe arranged in the assembled interlocking permeable carbon sequestration recycled concrete base and soil nails vertically penetrating from the assembled interlocking permeable carbon sequestration recycled concrete base to the carbon sequestration solidified mud slag base. When preparing the carbon sequestration solidified mud slag base, inject carbon dioxide with a concentration of 15-40% for carbonization curing; when preparing the permeable frame, inject carbon dioxide with a concentration of 15-40% three times respectively to achieve three carbon sequestrations; when preparing the carbon sequestration recycled fine aggregate leveling layer, inject carbon dioxide with a concentration of 15-40% for carbonization curing; when preparing the interlocking gap bricks, inject carbon dioxide with a concentration of 15-40% for carbonization curing. This technical solution uses the method of directly injecting high-concentration carbon dioxide into the material to achieve carbon sequestration. However, since high-concentration carbon dioxide cannot be continuously absorbed into the material, it cannot achieve the effect of long-term carbon sequestration. Also, since the amount of carbon dioxide absorbed by solid waste materials is limited, a large amount of carbon dioxide will be emitted during the injection process. Summary of the invention
[0007] In order to solve the problems existing in the prior art, the present invention provides an enhanced recycled aggregate cement concrete based on long-term carbon sequestration. The addition amount of each substance in the enhanced recycled aggregate cement concrete accounts for the mass percentage of the enhanced recycled aggregate cement concrete, which is 45-50wt% of recycled aggregate component, 2-5wt% of activated carbon capture agent, 1-2wt% of microencapsulated material, 24-28wt% of river sand, 0.8-1.2wt% of water reducer, 15-18wt% of cement, 1.2-4.8wt% of auxiliary admixture and 6-9wt% of water.
[0008] Preferably, the added amount of each substance in the recycled aggregate component accounts for 40-60wt% of the mass percentage of the recycled aggregate component, and the recycled aggregate is 40-60wt%; the aggregate includes any one or more of limestone, basalt, granite, and diabase; the recycled aggregate is low-brick-concrete construction waste recycled aggregate, that is, construction waste generated by the demolition of concrete buildings, and its brick-concrete content is 5-10wt%.
[0009] In any of the above schemes, it is preferred that the aggregate includes four particle sizes, and the mass percentage of each particle size in the aggregate is 8-11wt% for a particle size greater than or equal to 19mm, 34-50wt% for a particle size of 16-19mm, 35-51wt% for a particle size of 9.5-16mm, and 4-6wt% for a particle size of 4.75-9.5mm; the recycled aggregate includes four particle sizes, and the mass percentage of each particle size in the recycled aggregate is 8-11wt% for a particle size greater than or equal to 19mm, 34-50wt% for a particle size of 16-19mm, 35-51wt% for a particle size of 9.5-16mm, and 4-6wt% for a particle size of 4.75-9.5mm.
[0010] In any of the above schemes, it is preferred that the added amount of each substance in the activated carbon capture agent accounts for the mass percentage of the activated carbon capture agent, modified magnesium oxide 40-50wt%, calcium hydroxide component 20-30wt%, silicate 10-20wt%, catalyst 5-10wt%, industrial solid waste 5-10wt%, trace enhancer 1-3wt%.
[0011] In any of the above schemes, it is preferred that the added amount of each substance in the calcium hydroxide component accounts for the mass percentage of the calcium hydroxide component, calcium hydroxide 95-98.5wt%, metal oxide 1-3wt%, rare earth element 0.5-2wt%, the metal oxide is Al2O3 and / or Fe2O3, the rare earth element is Ce and / or La, and the particle size of the calcium hydroxide, the metal oxide and the rare earth element is 0.1-1μm.
[0012] In any of the above schemes, it is preferred that the silicate includes any one or more of anhydrous sodium silicate, potassium silicate, sodium potassium silicate, and sodium potassium composite silicate; the catalyst includes any one or more of titanium oxide, zirconium dioxide, magnesium aluminum layered double hydroxide, and hydrated magnesium aluminate carbonate; the industrial solid waste includes any one or more of steel slag, carbide slag, fly ash, desulfurized gypsum, red mud, and glass slag; the trace enhancer is a lithium-based compound and / or a manganese-based compound, the lithium-based compound includes any one or more of lithium carbonate, lithium hydroxide, and lithium chloride, and the manganese-based compound includes any one or more of manganese dioxide, manganese chloride, and potassium manganate.
[0013] In any of the above schemes, it is preferred that the amount of each substance added in the microencapsulation material accounts for 20-30wt% of chitosan, 50-60wt% of polylactic acid, and 20-30wt% of silica microspheres in the mass percentage of the microencapsulation material, and the ratio of the mass of the chitosan to the mass of the polylactic acid is 1:2.2-3, and the particle size of the silica microspheres is 0.01-10μm.
[0014] In any of the above schemes, it is preferred that the river sand includes eight particle sizes, and the mass percentage of each particle size in the river sand is: particle size 4.75-9.5mm accounts for 7-9wt%, particle size 2.36-4.75mm accounts for 3-5wt%, particle size 1.18-2.36mm accounts for 10-16wt%, particle size 0.6-1.18mm accounts for 15-25wt%, particle size 0.3-0.6mm accounts for 25-35wt%, particle size 0.15-0.3mm accounts for 20-30wt%, particle size 0.075-0.15mm accounts for 4-6wt%, and particle size 0-0.075mm accounts for 4-6wt%.
[0015] In any of the above schemes, it is preferred that the water reducer is a high-performance polycarboxylate water reducer, the cement is PO 42.5 ordinary Portland cement, and the auxiliary admixtures include any one or more of fly ash, slag powder, and silica fume.
[0016] The present invention also provides a method for preparing an enhanced recycled aggregate cement concrete based on long-term carbon sequestration, which is used to prepare the enhanced recycled aggregate cement concrete based on long-term carbon sequestration as described above, and comprises the following steps in order:
[0017] Step 1: prepare recycled aggregate components, activated carbon capture agent, and microencapsulation material respectively according to the designed material ratio and process parameters;
[0018] Step 2: Weigh the recycled aggregate components, activated carbon capture agent, microencapsulated material, river sand of various particle sizes, water reducer, cement, auxiliary admixtures and water according to the designed material ratio;
[0019] Step 3: adding part of the activated carbon capture agent to the microencapsulation material and stirring evenly, so that the activated carbon capture agent is wrapped inside the microencapsulation material to form a microcapsule raw material liquid; using a spray drying method to disperse the microcapsule raw material liquid into fine droplets, and quickly evaporate the solvent in a high-temperature hot air flow, so that the solid matter in the microcapsule raw material liquid is polymerized and solidified to form microcapsule particles;
[0020] Step 4: Put the recycled aggregate component and the remaining part of the activated carbon capture agent into a mechanical mixer for stirring. After stirring evenly, take out the mixture of the recycled aggregate component and the activated carbon capture agent from the mechanical mixer for standby use;
[0021] Step 5: sequentially put river sand of each particle size, cement, a mixture of recycled aggregate components and an activated carbon capture agent, and auxiliary admixtures into a mixing pot for mixing, and set aside after mixing evenly;
[0022] Step 6: Put water and a water reducing agent into a container and mix them evenly to form a mixed solution of water and the water reducing agent; put the mixed solution of water and the water reducing agent into a mixing pot and mix it together with the materials in the mixing pot, and after mixing evenly, obtain an enhanced recycled aggregate cement concrete slurry based on carbon sequestration;
[0023] Step 7: taking out the obtained carbon sequestration-based enhanced recycled aggregate cement concrete slurry from the mixing pot, putting it into a storage container, and performing manual mixing at the same time; after the manual mixing is completed, filling the carbon sequestration-based enhanced recycled aggregate cement concrete slurry into the specimen forming mold, and using a scraper to scrape the upper surface of the slurry in the specimen forming mold flat, and then evenly spreading part of the microcapsule particles on the upper surface of the slurry, and using a scraper to scrape the upper surface of the microcapsule particles flat;
[0024] Step 8: Place the specimen molding mold on an electric vibration table, start the electric vibration table, and start vibration molding. During the vibration molding process, if a depression occurs, add the carbon-sequestered enhanced recycled aggregate cement concrete slurry to the depressed part; after the vibration molding is completed, let the specimen molding mold and the formed slurry inside it stand for a certain period of time before demolding, and then put it into a standard curing room for curing to obtain a carbon-sequestered enhanced recycled aggregate cement concrete specimen;
[0025] Step nine: dissolve the remaining microcapsule particles in anhydrous ethanol to form a suspension; stir the suspension evenly and evenly coat the suspension on the outer surface of the enhanced recycled aggregate cement concrete specimen based on carbon sequestration to obtain an enhanced recycled aggregate cement concrete specimen based on long-term carbon sequestration.
[0026] Preferably, in step 1, the preparation process of the recycled aggregate component is: firstly, the construction waste generated by the demolition of concrete buildings is crushed and cleaned, and sieved according to the designed particle size grades to obtain recycled aggregates of various particle sizes; then, the recycled aggregates of various particle sizes are weighed according to the designed material ratio, and carbonization pretreatment is performed, that is, the recycled aggregates of various particle sizes are soaked in a sodium carbonate solution with a concentration of 5%, and the sodium carbonate solution is sufficient to cover the recycled aggregates of various particle sizes, and the soaking temperature is room temperature and the soaking time is 1-2h, after the soaking is completed, melamine is added to the sodium carbonate solution and the recycled aggregates of each particle size and stirred, the amount of melamine added is 0.5-1wt% of the total mass of the recycled aggregate, the stirring temperature is room temperature, and the stirring time is 0.5-1h. After the stirring is completed, the carbonization pretreatment of the recycled aggregate is completed; finally, according to the designed material ratio, the aggregates of each particle size are weighed, and the aggregates of each particle size and the recycled aggregates of each particle size after carbonization pretreatment are evenly mixed to obtain the recycled aggregate component.
[0027] In any of the above schemes, preferably, in step 1, the preparation process of the activated carbon capture agent is: first prepare modified magnesium oxide, that is, put the magnesium oxide into a calcining furnace for low-temperature calcination, the calcination temperature is 700-900°C, the calcination time is 3-5h, the calcined magnesium oxide is washed and purified, and the washed and purified magnesium oxide is placed in an oven for drying, the drying temperature is 80-100°C, and the drying time is 2-3h, and alkaline carbonate is added to the dried magnesium oxide and mixed evenly to obtain modified magnesium oxide, the addition amount of alkaline carbonate is 1-3wt% of the mass of the modified magnesium oxide, and the alkaline carbonate includes lithium carbonate. , potassium carbonate, cesium carbonate or any one or more thereof; secondly, prepare the calcium hydroxide component, that is, mix the calcium hydroxide, metal oxides and rare earth elements uniformly at room temperature according to the designed material ratio; then, according to the designed material ratio, mix the modified magnesium oxide, calcium hydroxide component, silicate, catalyst, industrial solid waste and trace enhancer uniformly at room temperature, and ball-mill the mixed material to obtain a solid powder with a particle size of less than 5 μm; finally, put the solid powder into an oven for drying at a temperature of 80-100°C and a drying time of 2-3h. After the drying process is completed, the activated carbon capture agent can be obtained.
[0028] In any of the above schemes, preferably, in step 1, the preparation process of the microencapsulated material is: first, chitosan, polylactic acid, and silica microspheres are weighed according to the designed material ratio for use; then, the chitosan and polylactic acid are mixed evenly and then dissolved in anhydrous ethanol to form a solution, wherein the mass of the anhydrous ethanol is 20-30 times the total mass of the chitosan and polylactic acid; finally, the silica microspheres are added to the solution and stirred evenly to obtain the microencapsulated material.
[0029] In any of the above schemes, preferably, in step three, the mass of the partial activated carbon capture agent is 40-50wt% of the total mass of the activated carbon capture agent, the temperature of the high-temperature hot air flow is 150-200°C, and the particle size of the microcapsule particles is 100-120μm.
[0030] In any of the above schemes, preferably, in step 4, the mass of the remaining part of the activated carbon capture agent is 50-60wt% of the total mass of the activated carbon capture agent; the stirring temperature of the mechanical stirrer is room temperature, the stirring speed is 120-180rpm, and the stirring time is 4-6min.
[0031] In any of the above schemes, preferably, in step five, the mixing temperature of the mixing pot is room temperature, the mixing speed is 40-60 rpm, and the mixing time is 60-90 s.
[0032] In any of the above schemes, preferably, in step six, the mixing temperature of the mixing pot is room temperature, the mixing speed is 40-60 rpm, and the mixing time is 3-4 min.
[0033] In any of the above schemes, it is preferred that in step seven, the mixing temperature of the manual mixing is room temperature and the mixing time is 1-2 minutes; the length of the inner cavity of the specimen molding mold is 100 mm, the width is 100 mm, and the height is 100 mm; the mass of the part of the microcapsule particles is 20-30wt% of the total mass of the microcapsule particles.
[0034] In any of the above schemes, it is preferred that in step eight, the standing temperature is room temperature, the standing time is 24 hours, and the curing time is 28 days.
[0035] In any of the above schemes, preferably, in step nine, the mass of the remaining microcapsule particles is 70-80wt% of the total mass of the microcapsule particles, and the mass of the anhydrous ethanol is 20-30 times the mass of the remaining microcapsule particles.
[0036] In the present invention, the mechanical stirrer, mixing pot, electric vibration table, calcining furnace, oven, etc. used are all traditional equipment in this field, and there are no special requirements for the model and structure of the equipment; the spray drying method adopted is also a traditional method in this field, and there are no special requirements for the process flow and process parameters, as long as the temperature of the high-temperature hot air flow is guaranteed to be within the range of 150-200°C.
[0037] Both aggregates and recycled aggregates include four particle sizes, namely particle size greater than or equal to 19mm, particle size 16-19mm, particle size 9.5-16mm, and particle size 4.75-9.5mm, that is, particle size ≥19mm, 16mm≤particle size<19mm, 9.5mm≤particle size<16mm, 4.75mm≤particle size<9.5mm. River sand includes eight particle sizes, namely 4.75-9.5mm, 2.36-4.75mm, 1.18-2.36mm, 0.6-1.18mm, 0.3-0.6mm, 0.15-0.3mm, 0.075-0.15mm and 0-0.075mm, that is, 4.75mm≤particle size<9.5mm, 2.36mm≤particle size<4.75mm, 1.18mm≤particle size<2.36mm, 0.6mm≤particle size<1.18mm, 0.3mm≤particle size<0.6mm, 0.15mm≤particle size<0.3mm, 0.075mm≤particle size<0.15mm and 0mm≤particle size<0.075mm. For each particle size, the material passes through the upper and lower sieve holes in sequence to obtain a particle size between the upper and lower sieve holes, for example: the particle size is 1.18-2.36mm (1.18mm≤particle size<2.36mm), that is, the material passes through the 2.36mm sieve hole and the 1.18mm sieve hole in sequence to obtain a particle size between 1.18-2.36mm.
[0038] In the process of preparing modified magnesium oxide, magnesium oxide is excited by low-temperature calcination; in the process of preparing calcium hydroxide components, calcium hydroxide is excited by adding metal oxides and rare earth elements. The metal oxides can make calcium hydroxide absorb more carbon dioxide, and the rare earth elements can make the absorbed carbon dioxide produce calcium carbonate crystals and make the calcium carbonate crystals grow evenly; carbonization pretreatment of recycled aggregates of various particle sizes can increase the contact area between the recycled aggregates and carbon dioxide.
[0039] In the present invention, in the preparation process of recycled aggregate components, activated carbon capture agents, and microencapsulated materials, the selection of each substance, the addition amount of each substance, the addition order of each substance, the process parameters of each step, etc. are very critical. At the same time, in the entire preparation process of enhanced recycled aggregate cement concrete, the selection of each substance, the addition amount of each substance, the addition order of each substance, the process parameters of each step, etc. are also very critical. Only by synergizing various formula parameters and process parameters can the expected technical effect of the present invention be achieved.
[0040] The enhanced recycled aggregate cement concrete based on long-term carbon sequestration and the preparation method of the present invention have the following beneficial effects:
[0041] (1) The recycled aggregate cement concrete obtained by the material ratio and preparation process of the present invention can not only continuously adsorb and store carbon dioxide, but also significantly improve the overall performance of the recycled aggregate cement concrete, such as strength and durability.
[0042] (2) The present invention improves the ability of recycled aggregate cement concrete to continuously absorb carbon dioxide and store carbon for a long time during its long service life by introducing microencapsulated carbon capture agents.
[0043] (3) The present invention performs carbonization pretreatment on recycled aggregates of various particle sizes to enhance their interfacial bonding properties and the ability to efficiently capture carbon dioxide; at the same time, the present invention combines carbon capture activators with microencapsulated carbon sequestration materials to achieve dynamic carbon capture and long-term carbon sequestration capabilities of recycled aggregate cement concrete during its service life.
[0044] (4) The present invention solves the problems of low strength and poor interface bonding performance of traditional recycled aggregates, and has broad application prospects in the fields of green building and low-carbon infrastructure construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 It is a flow chart of a preferred embodiment of a method for preparing enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to the present invention;
[0046] Figure 2 for Figure 1 A real photo of the activated carbon capture agent prepared in the illustrated embodiment;
[0047] Figure 3 for Figure 1 Actual photos of microencapsulated materials prepared in the examples shown;
[0048] Figure 4 for Figure 1 Actual photographs of the long-term carbon sequestration enhanced recycled aggregate cement concrete specimens prepared in the illustrated embodiment;
[0049] Figure 5 These are SEM photos of the long-term carbon sequestration enhanced recycled aggregate cement concrete specimens of Example 1 after 28 days of standard curing and 6 months of outdoor exposure, where: (a) is 28 days of standard curing, and (b) is 6 months of outdoor exposure;
[0050] Figure 6 The SEM photos of the ordinary recycled aggregate cement concrete specimens of Comparative Example 2 after standard curing for 28 days and outdoor exposure for 6 months, where: (a) is standard curing for 28 days, and (b) is outdoor exposure for 6 months;
[0051] Figure 7 XRD photos of the long-term carbon sequestration enhanced recycled aggregate cement concrete specimen of Example 1 after standard curing for 28 days and outdoor exposure for 6 months, where: (a) is standard curing for 28 days, and (b) is outdoor exposure for 6 months;
[0052] Figure 8 These are XRD photographs of the ordinary recycled aggregate cement concrete specimens of Comparative Example 2 after standard curing for 28 days and outdoor exposure for 6 months, where: (a) is standard curing for 28 days, and (b) is outdoor exposure for 6 months. DETAILED DESCRIPTION
[0053] In order to further understand the content of the present invention, the present invention will be described in detail below in conjunction with specific embodiments.
[0054] Embodiment 1:
[0055] According to a preferred embodiment of the enhanced recycled aggregate cement concrete based on long-term carbon sequestration of the present invention, the addition amount of each substance in the enhanced recycled aggregate cement concrete is as follows: 47wt% of recycled aggregate component, 3wt% of activated carbon capture agent, 1wt% of microencapsulated material, 24wt% of river sand, 1wt% of water reducer, 15wt% of cement, 3wt% of auxiliary admixture and 6wt% of water.
[0056] The added amount of each substance in the recycled aggregate component accounts for 50wt% of the mass percentage of the recycled aggregate component, 50wt% of aggregate and 50wt% of recycled aggregate; the aggregate is limestone, and the recycled aggregate is low-brick-concrete construction waste recycled aggregate, that is, construction waste generated by the demolition of concrete buildings, and its brick-concrete content is 5-10wt%.
[0057] The aggregate includes four particle sizes, and the mass percentage of each particle size is as follows: particle size greater than or equal to 19 mm accounts for 10wt%, particle size 16-19 mm accounts for 42wt%, particle size 9.5-16mm accounts for 43wt%, and particle size 4.75-9.5mm accounts for 5wt%; the recycled aggregate includes four particle sizes, and the mass percentage of each particle size is as follows: particle size greater than or equal to 19 mm accounts for 10wt%, particle size 16-19 mm accounts for 42wt%, particle size 9.5-16mm accounts for 43wt%, and particle size 4.75-9.5mm accounts for 5wt%.
[0058] The added amounts of various substances in the activated carbon capture agent are as follows: 45wt% of modified magnesium oxide, 25wt% of calcium hydroxide component, 15wt% of silicate, 7wt% of catalyst, 7wt% of industrial solid waste, and 1wt% of trace enhancer, based on the mass percentage of the activated carbon capture agent.
[0059] The added amount of each substance in the calcium hydroxide component is 97wt% of calcium hydroxide, 2wt% of metal oxide, and 1wt% of rare earth element in mass percentage of the calcium hydroxide component. The metal oxide is Al2O3, the rare earth element is Ce, and the particle size of the calcium hydroxide, the metal oxide, and the rare earth element is 0.5μm. The silicate is anhydrous sodium silicate, the catalyst is magnesium aluminum layered double hydroxide, the industrial solid waste is steel slag, the trace enhancer is a lithium-based compound, and the lithium-based compound is lithium carbonate.
[0060] The mass percentage of each substance added in the microencapsulation material is chitosan 20wt%, polylactic acid 60wt%, and silica microspheres 20wt%, and the ratio of the mass of the chitosan to the mass of the polylactic acid is 1:3, ensuring that it is within the range of 1:2.2-3, and the particle size of the silica microspheres is 5μm.
[0061] The river sand includes eight particle sizes, and the mass percentage of each particle size is as follows: 7wt% of the particle size is 4.75-9.5mm, 3wt% of the particle size is 2.36-4.75mm, 10wt% of the particle size is 1.18-2.36mm, 20wt% of the particle size is 0.6-1.18mm, 25wt% of the particle size is 0.3-0.6mm, 25wt% of the particle size is 0.15-0.3mm, 5wt% of the particle size is 0.075-0.15mm, and 5wt% of the particle size is 0-0.075mm. The water reducer is a high-performance polycarboxylate water reducer, the cement is PO 42.5 ordinary Portland cement, and the auxiliary admixture is fly ash.
[0062] like Figure 1 As shown, this embodiment also provides a method for preparing an enhanced recycled aggregate cement concrete based on long-term carbon sequestration, which is used to prepare the above-mentioned enhanced recycled aggregate cement concrete based on long-term carbon sequestration, and includes the following steps in order:
[0063] Step 1: prepare recycled aggregate components, activated carbon capture agent, and microencapsulation material respectively according to the designed material ratio and process parameters;
[0064] Step 2: Weigh the recycled aggregate components, activated carbon capture agent, microencapsulated material, river sand of various particle sizes, water reducer, cement, auxiliary admixtures and water according to the designed material ratio;
[0065] Step 3: adding part of the activated carbon capture agent to the microencapsulation material and stirring evenly, so that the activated carbon capture agent is wrapped inside the microencapsulation material to form a microcapsule raw material liquid; using a spray drying method to disperse the microcapsule raw material liquid into fine droplets, and quickly evaporate the solvent in a high-temperature hot air flow, so that the solid matter in the microcapsule raw material liquid is polymerized and solidified to form microcapsule particles;
[0066] Step 4: Put the recycled aggregate component and the remaining part of the activated carbon capture agent into a mechanical mixer for stirring. After stirring evenly, take out the mixture of the recycled aggregate component and the activated carbon capture agent from the mechanical mixer for standby use;
[0067] Step 5: sequentially put river sand of each particle size, cement, a mixture of recycled aggregate components and an activated carbon capture agent, and auxiliary admixtures into a mixing pot for mixing, and set aside after mixing evenly;
[0068] Step 6: Put water and a water reducing agent into a container and mix them evenly to form a mixed solution of water and the water reducing agent; put the mixed solution of water and the water reducing agent into a mixing pot and mix it together with the materials in the mixing pot, and after mixing evenly, obtain an enhanced recycled aggregate cement concrete slurry based on carbon sequestration;
[0069] Step 7: taking out the obtained carbon sequestration-based enhanced recycled aggregate cement concrete slurry from the mixing pot, putting it into a storage container, and performing manual mixing at the same time; after the manual mixing is completed, filling the carbon sequestration-based enhanced recycled aggregate cement concrete slurry into the specimen forming mold, and using a scraper to scrape the upper surface of the slurry in the specimen forming mold flat, and then evenly spreading part of the microcapsule particles on the upper surface of the slurry, and using a scraper to scrape the upper surface of the microcapsule particles flat;
[0070] Step 8: Place the specimen molding mold on an electric vibration table, start the electric vibration table, and start vibration molding. During the vibration molding process, if a depression occurs, add the carbon-sequestered enhanced recycled aggregate cement concrete slurry to the depressed part; after the vibration molding is completed, let the specimen molding mold and the formed slurry inside it stand for a certain period of time before demolding, and then put it into a standard curing room for curing to obtain a carbon-sequestered enhanced recycled aggregate cement concrete specimen;
[0071] Step nine: dissolve the remaining microcapsule particles in anhydrous ethanol to form a suspension; stir the suspension evenly and evenly coat the suspension on the outer surface of the enhanced recycled aggregate cement concrete specimen based on carbon sequestration to obtain an enhanced recycled aggregate cement concrete specimen based on long-term carbon sequestration.
[0072] In step 1, the preparation process of the recycled aggregate component is as follows: first, the construction waste generated by the demolition of concrete buildings is crushed and cleaned, and sieved according to the designed particle size grades to obtain recycled aggregates of various particle sizes; then, the recycled aggregates of various particle sizes are weighed according to the designed material ratio, and carbonization pretreatment is performed, that is, the recycled aggregates of various particle sizes are soaked in a sodium carbonate solution with a concentration of 5%, and the sodium carbonate solution is sufficient to cover the recycled aggregates of various particle sizes, and the soaking temperature is room temperature and the soaking time is 1.5h, after the soaking is completed, melamine is added to the sodium carbonate solution and the recycled aggregate of each particle size and stirred, the amount of melamine added is 0.8wt% of the total mass of the recycled aggregate, the stirring temperature is room temperature, and the stirring time is 0.8h. After the stirring is completed, the carbonization pretreatment of the recycled aggregate is completed; finally, according to the designed material ratio, the aggregate of each particle size is weighed, and the aggregate of each particle size and the recycled aggregate of each particle size after carbonization pretreatment are evenly mixed to obtain the recycled aggregate component.
[0073] In step 1, the preparation process of the activated carbon capture agent is as follows: first, modified magnesium oxide is prepared, that is, magnesium oxide is placed in a calcining furnace for low-temperature calcination, the calcination temperature is 800°C, the calcination time is 4h, the calcined magnesium oxide is washed and purified, and the washed and purified magnesium oxide is placed in an oven for drying, the drying temperature is 90°C, and the drying time is 2.5h, and alkaline carbonate is added to the dried magnesium oxide and mixed evenly to obtain modified magnesium oxide, the addition amount of alkaline carbonate is 2wt% of the mass of the modified magnesium oxide, and the alkaline carbonate is lithium carbonate; secondly The calcium hydroxide component is prepared, that is, calcium hydroxide, metal oxides, and rare earth elements are mixed uniformly at room temperature according to the designed material ratio; then modified magnesium oxide, calcium hydroxide component, silicate, catalyst, industrial solid waste, and trace enhancer are mixed uniformly at room temperature according to the designed material ratio, and the mixed material is ball-milled to obtain a solid powder with a particle size of less than 5 μm; finally, the solid powder is placed in an oven for drying at a drying temperature of 90° C. and a drying time of 2.5 hours. After the drying process is completed, an activated carbon capture agent can be obtained.
[0074] In step 1, the preparation process of the microencapsulated material is as follows: first, chitosan, polylactic acid, and silica microspheres are weighed according to the designed material ratio for use; then, the chitosan and polylactic acid are mixed evenly and put into anhydrous ethanol to dissolve to form a solution, wherein the mass of the anhydrous ethanol is 25 times the total mass of the chitosan and polylactic acid; finally, the silica microspheres are added to the solution and stirred evenly to obtain the microencapsulated material.
[0075] In step three, the mass of the part of the activated carbon capture agent is 45wt% of the total mass of the activated carbon capture agent, the temperature of the high-temperature hot air flow is 180°C, and the particle size of the microcapsule particles is 110μm.
[0076] In step 4, the mass of the remaining activated carbon capture agent is 55wt% of the total mass of the activated carbon capture agent; the stirring temperature of the mechanical stirrer is room temperature, the stirring speed is 150rpm, and the stirring time is 5min.
[0077] In step 5, the mixing temperature of the mixing pot is room temperature, the mixing speed is 50 rpm, and the mixing time is 75 s.
[0078] In step six, the mixing temperature of the mixing pot is room temperature, the mixing speed is 50 rpm, and the mixing time is 3.5 min.
[0079] In step seven, the mixing temperature of manual mixing is room temperature and the mixing time is 1.5 min; the inner cavity of the specimen molding mold has a length of 100 mm, a width of 100 mm, and a height of 100 mm; and the mass of the partial microcapsule particles is 25 wt% of the total mass of the microcapsule particles.
[0080] In step eight, the standing temperature is room temperature, the standing time is 24 hours, and the curing time is 28 days.
[0081] In step nine, the mass of the remaining microcapsule particles is 75wt% of the total mass of the microcapsule particles, and the mass of the anhydrous ethanol is 25 times the mass of the remaining microcapsule particles.
[0082] In this embodiment, the actual photo of the prepared activated carbon capture agent is as follows: Figure 2 The actual photo of the prepared microencapsulated material is shown in Figure 3 The actual photo of the prepared long-term carbon sequestration enhanced recycled aggregate cement concrete specimen is shown in Figure 4 shown.
[0083] In this embodiment, the mechanical stirrer, mixing pot, electric vibration table, calcining furnace, oven, etc. used are all traditional equipment in this field, and there are no special requirements for the model and structure of the equipment; the spray drying method used is also a traditional method in this field, and there are no special requirements for the process flow and process parameters, as long as the temperature of the high-temperature hot air flow is guaranteed to be within the range of 150-200°C.
[0084] Both aggregates and recycled aggregates include four particle sizes, namely particle size greater than or equal to 19mm, particle size 16-19mm, particle size 9.5-16mm, and particle size 4.75-9.5mm, that is, particle size ≥19mm, 16mm≤particle size<19mm, 9.5mm≤particle size<16mm, 4.75mm≤particle size<9.5mm. River sand includes eight particle sizes, namely 4.75-9.5mm, 2.36-4.75mm, 1.18-2.36mm, 0.6-1.18mm, 0.3-0.6mm, 0.15-0.3mm, 0.075-0.15mm and 0-0.075mm, that is, 4.75mm≤particle size<9.5mm, 2.36mm≤particle size<4.75mm, 1.18mm≤particle size<2.36mm, 0.6mm≤particle size<1.18mm, 0.3mm≤particle size<0.6mm, 0.15mm≤particle size<0.3mm, 0.075mm≤particle size<0.15mm and 0mm≤particle size<0.075mm. For each particle size, the material passes through the upper and lower sieve holes in sequence to obtain a particle size between the upper and lower sieve holes, for example: the particle size is 1.18-2.36mm (1.18mm≤particle size<2.36mm), that is, the material passes through the 2.36mm sieve hole and the 1.18mm sieve hole in sequence to obtain a particle size between 1.18-2.36mm.
[0085] In the process of preparing modified magnesium oxide, magnesium oxide is excited by low-temperature calcination; in the process of preparing calcium hydroxide components, calcium hydroxide is excited by adding metal oxides and rare earth elements. The metal oxides can make calcium hydroxide absorb more carbon dioxide, and the rare earth elements can make the absorbed carbon dioxide produce calcium carbonate crystals and make the calcium carbonate crystals grow evenly; carbonization pretreatment of recycled aggregates of various particle sizes can increase the contact area between the recycled aggregates and carbon dioxide.
[0086] In this embodiment, in the preparation process of recycled aggregate components, activated carbon capture agents, and microencapsulated materials, the selection of each substance, the amount of each substance added, the order of addition of each substance, the process parameters of each step, etc. are very critical. At the same time, in the entire preparation process of enhanced recycled aggregate cement concrete, the selection of each substance, the amount of each substance added, the order of addition of each substance, the process parameters of each step, etc. are also very critical. Only by synergizing the various formula parameters and process parameters can the expected technical effect of this embodiment be achieved.
[0087] The enhanced recycled aggregate cement concrete and preparation method based on long-term carbon sequestration in this embodiment have the following beneficial effects:
[0088] (1) The prepared recycled aggregate cement concrete can not only continuously absorb and store carbon dioxide, but also significantly improve the overall performance of recycled aggregate cement concrete, such as strength and durability. (2) By introducing microencapsulated carbon capture agents, the ability of recycled aggregate cement concrete to continuously absorb carbon dioxide and store carbon for a long time during its service life is improved. (3) By carbonization pretreatment of recycled aggregates of various particle sizes, they are able to enhance interfacial bonding properties and efficiently capture carbon dioxide; at the same time, by combining carbon capture activators with microencapsulated carbon storage materials, the dynamic carbon capture and long-term carbon storage capabilities of recycled aggregate cement concrete during its service life are achieved.
[0089] Embodiment 2:
[0090] According to another preferred embodiment of the enhanced recycled aggregate cement concrete and preparation method based on long-term carbon sequestration of the present invention, its material ratio, preparation process, technical principle, equipment used, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0091] The added amounts of various substances in the enhanced recycled aggregate cement concrete are as follows: 45wt% of recycled aggregate component, 2wt% of activated carbon capture agent, 1wt% of microencapsulated material, 24wt% of river sand, 0.8wt% of water reducer, 18wt% of cement, 1.2wt% of auxiliary admixture, and 8wt% of water, as a percentage of the mass of the enhanced recycled aggregate cement concrete.
[0092] The mass percentage of each substance added in the recycled aggregate component is 40wt% of aggregate and 60wt% of recycled aggregate; the aggregate is limestone, and the recycled aggregate is low-brick-concrete construction waste recycled aggregate, that is, construction waste generated by the demolition of concrete buildings, and its brick-concrete content is 5-10wt%. The aggregate includes four particle sizes, and the mass percentage of each particle size in the aggregate is 11wt% for particle size greater than or equal to 19mm, 50wt% for particle size 16-19mm, 35wt% for particle size 9.5-16mm, and 4wt% for particle size 4.75-9.5mm; the recycled aggregate includes four particle sizes, and the mass percentage of each particle size in the recycled aggregate is 11wt% for particle size greater than or equal to 19mm, 50wt% for particle size 16-19mm, 35wt% for particle size 9.5-16mm, and 4wt% for particle size 4.75-9.5mm.
[0093] The added amount of each substance in the activated carbon capture agent accounts for the mass percentage of the activated carbon capture agent, which is 40wt% of modified magnesium oxide, 20wt% of calcium hydroxide component, 20wt% of silicate, 10wt% of catalyst, 8wt% of industrial solid waste, and 2wt% of trace enhancer. The added amount of each substance in the calcium hydroxide component accounts for the mass percentage of the calcium hydroxide component, which is 95wt% of calcium hydroxide, 3wt% of metal oxide, and 2wt% of rare earth element. The metal oxide is Al2O3, the rare earth element is Ce, and the particle size of the calcium hydroxide, the metal oxide, and the rare earth element is 1μm. The silicate is anhydrous sodium silicate, the catalyst is magnesium aluminum layered double hydroxide, the industrial solid waste is steel slag, the trace enhancer is a lithium-based compound, and the lithium-based compound is lithium carbonate.
[0094] The mass percentage of each substance added in the microencapsulation material is chitosan 25wt%, polylactic acid 55wt%, and silica microspheres 20wt%, and the ratio of the mass of the chitosan to the mass of the polylactic acid is 1:2.2, ensuring that it is within the range of 1:2.2-3, and the particle size of the silica microspheres is 10μm.
[0095] The river sand includes eight particle sizes, and the mass percentage of each particle size is as follows: 8wt% of the particle size is 4.75-9.5mm, 4wt% of the particle size is 2.36-4.75mm, 13wt% of the particle size is 1.18-2.36mm, 15wt% of the particle size is 0.6-1.18mm, 32wt% of the particle size is 0.3-0.6mm, 20wt% of the particle size is 0.15-0.3mm, 4wt% of the particle size is 0.075-0.15mm, and 4wt% of the particle size is 0-0.075mm. The water reducer is a high-performance polycarboxylate water reducer, the cement is PO 42.5 ordinary Portland cement, and the auxiliary admixture is fly ash.
[0096] In step one, during the preparation of the recycled aggregate component: the recycled aggregates of various particle sizes are soaked in a sodium carbonate solution with a concentration of 5%, and the sodium carbonate solution is sufficient to cover the recycled aggregates of various particle sizes. The soaking temperature is room temperature and the soaking time is 2 hours. After the soaking is completed, melamine is added to the sodium carbonate solution and the recycled aggregates of various particle sizes and stirred. The amount of melamine added is 1wt% of the total mass of the recycled aggregates. The stirring temperature is room temperature and the stirring time is 1 hour. After the stirring is completed, the carbonization pretreatment of the recycled aggregates is completed.
[0097] In the preparation process of the activated carbon capture agent: firstly, modified magnesium oxide is prepared, that is, magnesium oxide is placed in a calcining furnace for low-temperature calcination, the calcination temperature is 900°C, and the calcination time is 3h, the calcined magnesium oxide is washed and purified, and the washed and purified magnesium oxide is placed in an oven for drying treatment, the drying temperature is 100°C, and the drying time is 2h, and alkaline carbonate is added to the dried magnesium oxide and mixed evenly to obtain modified magnesium oxide, the addition amount of alkaline carbonate is 3wt% of the mass of the modified magnesium oxide, and the alkaline carbonate is lithium carbonate; finally, the solid powder is placed in an oven for drying treatment, the drying temperature is 100°C, and the drying time is 2h, and after the drying treatment is completed, the activated carbon capture agent can be obtained.
[0098] In the preparation process of the microencapsulation material: chitosan and polylactic acid are mixed evenly and then put into anhydrous ethanol to dissolve to form a solution, and the mass of the anhydrous ethanol is 30 times the total mass of the chitosan and polylactic acid.
[0099] In step three, the mass of the part of the activated carbon capture agent is 50wt% of the total mass of the activated carbon capture agent, the temperature of the high-temperature hot air flow is 200°C, and the particle size of the microcapsule particles is 120μm.
[0100] In step 4, the mass of the remaining activated carbon capture agent is 50wt% of the total mass of the activated carbon capture agent; the stirring temperature of the mechanical stirrer is room temperature, the stirring speed is 180rpm, and the stirring time is 4min.
[0101] In step 5, the mixing temperature of the mixing pot is room temperature, the mixing speed is 60 rpm, and the mixing time is 60 s.
[0102] In step six, the mixing temperature of the mixing pot is room temperature, the mixing speed is 60 rpm, and the mixing time is 3 min.
[0103] In step seven, the mixing temperature of manual mixing is room temperature and the mixing time is 2 minutes; the inner cavity of the specimen molding mold has a length of 100 mm, a width of 100 mm, and a height of 100 mm; and the mass of the partial microcapsule particles is 30 wt% of the total mass of the microcapsule particles.
[0104] In step eight, the standing temperature is room temperature, the standing time is 24 hours, and the curing time is 28 days.
[0105] In step nine, the mass of the remaining microcapsule particles is 70wt% of the total mass of the microcapsule particles, and the mass of the anhydrous ethanol is 30 times the mass of the remaining microcapsule particles.
[0106] Embodiment three:
[0107] According to another preferred embodiment of the enhanced recycled aggregate cement concrete and preparation method based on long-term carbon sequestration of the present invention, its material ratio, preparation process, technical principle, equipment used, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0108] The added amounts of various substances in the enhanced recycled aggregate cement concrete are as follows: 48wt% of recycled aggregate component, 3.5wt% of activated carbon capture agent, 1.5wt% of microencapsulated material, 24wt% of river sand, 0.8wt% of water reducer, 15wt% of cement, 1.2wt% of auxiliary admixture and 6wt% of water, as percentage by mass of the enhanced recycled aggregate cement concrete.
[0109] The mass percentage of each substance added in the recycled aggregate component is 60wt% of aggregate and 40wt% of recycled aggregate; the aggregate is basalt, and the recycled aggregate is low-brick-concrete construction waste recycled aggregate, that is, construction waste generated by the demolition of concrete buildings, and its brick-concrete content is 5-10wt%. The aggregate includes four particle sizes, and the mass percentage of each particle size in the aggregate is 8wt% for particle size greater than or equal to 19mm, 35wt% for particle size 16-19mm, 51wt% for particle size 9.5-16mm, and 6wt% for particle size 4.75-9.5mm; the recycled aggregate includes four particle sizes, and the mass percentage of each particle size in the recycled aggregate is 8wt% for particle size greater than or equal to 19mm, 35wt% for particle size 16-19mm, 51wt% for particle size 9.5-16mm, and 6wt% for particle size 4.75-9.5mm.
[0110] The added amount of each substance in the activated carbon capture agent accounts for the mass percentage of the activated carbon capture agent, which is 50wt% of modified magnesium oxide, 27wt% of calcium hydroxide component, 10wt% of silicate, 5wt% of catalyst, 5wt% of industrial solid waste, and 3wt% of trace enhancer. The added amount of each substance in the calcium hydroxide component accounts for the mass percentage of the calcium hydroxide component, which is 98.5wt% of calcium hydroxide, 1wt% of metal oxide, and 1.5wt% of rare earth element. The metal oxide is Fe2O3, the rare earth element is La, and the particle size of the calcium hydroxide, the metal oxide, and the rare earth element is 0.1μm. The silicate is potassium silicate, the catalyst is hydrated magnesium aluminate carbonate, the industrial solid waste is desulfurized gypsum, the trace enhancer is a lithium-based compound, and the lithium-based compound is lithium hydroxide.
[0111] The mass percentage of each substance added in the microencapsulation material is chitosan 22wt%, polylactic acid 57wt%, and silica microspheres 21wt%, and the ratio of the mass of the chitosan to the mass of the polylactic acid is 1:2.59, ensuring that it is within the range of 1:2.2-3, and the particle size of the silica microspheres is 1μm.
[0112] The river sand includes eight particle sizes, and the mass percentage of each particle size is as follows: 9wt% of the particle size is 4.75-9.5mm, 5wt% of the particle size is 2.36-4.75mm, 10wt% of the particle size is 1.18-2.36mm, 20wt% of the particle size is 0.6-1.18mm, 28wt% of the particle size is 0.3-0.6mm, 20wt% of the particle size is 0.15-0.3mm, 4wt% of the particle size is 0.075-0.15mm, and 4wt% of the particle size is 0-0.075mm. The water reducer is a high-performance polycarboxylate water reducer, the cement is PO 42.5 ordinary Portland cement, and the auxiliary admixture is slag powder.
[0113] In step one, during the preparation of the recycled aggregate component: the recycled aggregates of each particle size are soaked in a sodium carbonate solution with a concentration of 5%, the sodium carbonate solution is sufficient to cover the recycled aggregates of each particle size, the soaking temperature is room temperature, and the soaking time is 1 hour. After the soaking is completed, melamine is added to the sodium carbonate solution and the recycled aggregates of each particle size and stirred. The amount of melamine added is 0.5wt% of the total mass of the recycled aggregates. The stirring temperature is room temperature and the stirring time is 0.5h. After the stirring is completed, the carbonization pretreatment of the recycled aggregates is completed.
[0114] In the preparation process of the activated carbon capture agent: firstly, modified magnesium oxide is prepared, that is, magnesium oxide is placed in a calcining furnace for low-temperature calcination, the calcination temperature is 700°C, and the calcination time is 5 hours, the calcined magnesium oxide is washed and purified, and the washed and purified magnesium oxide is placed in an oven for drying treatment, the drying temperature is 80°C, and the drying time is 3 hours, and alkaline carbonate is added to the dried magnesium oxide and mixed evenly to obtain modified magnesium oxide, the addition amount of alkaline carbonate is 1wt% of the mass of the modified magnesium oxide, and the alkaline carbonate is potassium carbonate; finally, the solid powder is placed in an oven for drying treatment, the drying temperature is 80°C, and the drying time is 3 hours. After the drying treatment is completed, the activated carbon capture agent can be obtained.
[0115] In the preparation process of the microencapsulation material: chitosan and polylactic acid are mixed evenly and then put into anhydrous ethanol to dissolve to form a solution, and the mass of the anhydrous ethanol is 20 times the total mass of the chitosan and polylactic acid.
[0116] In step three, the mass of the part of the activated carbon capture agent is 40wt% of the total mass of the activated carbon capture agent, the temperature of the high-temperature hot air flow is 150°C, and the particle size of the microcapsule particles is 100μm.
[0117] In step 4, the mass of the remaining part of the activated carbon capture agent is 60wt% of the total mass of the activated carbon capture agent; the stirring temperature of the mechanical stirrer is room temperature, the stirring speed is 120rpm, and the stirring time is 6min.
[0118] In step 5, the mixing temperature of the mixing pot is room temperature, the mixing speed is 40 rpm, and the mixing time is 90 s.
[0119] In step six, the mixing temperature of the mixing pot is room temperature, the mixing speed is 40 rpm, and the mixing time is 4 minutes.
[0120] In step seven, the mixing temperature of manual mixing is room temperature and the mixing time is 1 min; the inner cavity of the specimen molding mold has a length of 100 mm, a width of 100 mm, and a height of 100 mm; and the mass of the partial microcapsule particles is 20 wt% of the total mass of the microcapsule particles.
[0121] In step eight, the standing temperature is room temperature, the standing time is 24 hours, and the curing time is 28 days.
[0122] In step nine, the mass of the remaining microcapsule particles is 80wt% of the total mass of the microcapsule particles, and the mass of the anhydrous ethanol is 20 times the mass of the remaining microcapsule particles.
[0123] Embodiment 4:
[0124] According to another preferred embodiment of the enhanced recycled aggregate cement concrete and preparation method based on long-term carbon sequestration of the present invention, its material ratio, preparation process, technical principle, equipment used, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0125] The added amounts of various substances in the enhanced recycled aggregate cement concrete are as follows: 46wt% of recycled aggregate component, 5wt% of activated carbon capture agent, 2wt% of microencapsulated material, 24wt% of river sand, 0.8wt% of water reducer, 15wt% of cement, 1.2wt% of auxiliary admixture and 6wt% of water, as percentage by mass of the enhanced recycled aggregate cement concrete.
[0126] The mass percentage of each substance added in the recycled aggregate component is 45wt% of aggregate and 55wt% of recycled aggregate; the aggregate is diabase, and the recycled aggregate is low-brick-concrete construction waste recycled aggregate, that is, construction waste generated by the demolition of concrete buildings, and its brick-concrete content is 5-10wt%. The aggregate includes four particle sizes, and the mass percentage of each particle size in the aggregate is 9wt% for particle size greater than or equal to 19mm, 46wt% for particle size 16-19mm, 39wt% for particle size 9.5-16mm, and 6wt% for particle size 4.75-9.5mm; the recycled aggregate includes four particle sizes, and the mass percentage of each particle size in the recycled aggregate is 9wt% for particle size greater than or equal to 19mm, 46wt% for particle size 16-19mm, 39wt% for particle size 9.5-16mm, and 6wt% for particle size 4.75-9.5mm.
[0127] The added amount of each substance in the activated carbon capture agent accounts for the mass percentage of the activated carbon capture agent, which is 47wt% of modified magnesium oxide, 22wt% of calcium hydroxide component, 17wt% of silicate, 8wt% of catalyst, 5wt% of industrial solid waste, and 1wt% of trace enhancer. The added amount of each substance in the calcium hydroxide component accounts for the mass percentage of the calcium hydroxide component, which is 98wt% of calcium hydroxide, 1.5wt% of metal oxide, and 0.5wt% of rare earth element. The metal oxide is Al2O3, the rare earth element is Ce, and the particle size of the calcium hydroxide, the metal oxide, and the rare earth element is 0.8μm. The silicate is sodium potassium silicate, the catalyst is titanium oxide, the industrial solid waste is steel slag, and the trace enhancer is a manganese-based compound, and the manganese-based compound is manganese dioxide.
[0128] The addition amount of each substance in the microencapsulation material accounts for 20wt% of chitosan, 50wt% of polylactic acid, and 30wt% of silica microspheres in terms of the mass percentage of the microencapsulation material, and the ratio of the mass of the chitosan to the mass of the polylactic acid is 1:2.5, ensuring that it is within the range of 1:2.2-3, and the particle size of the silica microspheres is 8μm.
[0129] The river sand includes eight particle sizes, and the mass percentage of each particle size is as follows: particle size 4.75-9.5 mm accounts for 7wt%, particle size 2.36-4.75 mm accounts for 3wt%, particle size 1.18-2.36 mm accounts for 10wt%, particle size 0.6-1.18 mm accounts for 15wt%, particle size 0.3-0.6 mm accounts for 33wt%, particle size 0.15-0.3 mm accounts for 20wt%, particle size 0.075-0.15 mm accounts for 6wt%, and particle size 0-0.075 mm accounts for 6wt%. The water reducer is a high-performance polycarboxylate water reducer, the cement is PO 42.5 ordinary Portland cement, and the auxiliary admixture is silica fume.
[0130] In step one, during the preparation of the recycled aggregate component: the recycled aggregates of various particle sizes are soaked in a sodium carbonate solution with a concentration of 5%, and the sodium carbonate solution is sufficient to cover the recycled aggregates of various particle sizes. The soaking temperature is room temperature and the soaking time is 1.8 hours. After the soaking is completed, melamine is added to the sodium carbonate solution and the recycled aggregates of various particle sizes and stirred. The amount of melamine added is 0.9wt% of the total mass of the recycled aggregates. The stirring temperature is room temperature and the stirring time is 0.9h. After the stirring is completed, the carbonization pretreatment of the recycled aggregates is completed.
[0131] In the preparation process of the activated carbon capture agent: firstly, modified magnesium oxide is prepared, that is, magnesium oxide is placed in a calcining furnace for low-temperature calcination, the calcination temperature is 850°C, and the calcination time is 3.5 hours, the calcined magnesium oxide is washed and purified, and the washed and purified magnesium oxide is placed in an oven for drying treatment, the drying temperature is 95°C, and the drying time is 2.8 hours, and alkaline carbonate is added to the dried magnesium oxide and mixed evenly to obtain modified magnesium oxide, the addition amount of alkaline carbonate is 2.5wt% of the mass of the modified magnesium oxide, and the alkaline carbonate is lithium carbonate; finally, the solid powder is placed in an oven for drying treatment, the drying temperature is 95°C, and the drying time is 2.8 hours. After the drying treatment is completed, the activated carbon capture agent can be obtained.
[0132] In the preparation process of the microencapsulation material: chitosan and polylactic acid are mixed evenly and then put into anhydrous ethanol to dissolve to form a solution, and the mass of the anhydrous ethanol is 28 times the total mass of the chitosan and polylactic acid.
[0133] In step three, the mass of the part of the activated carbon capture agent is 48wt% of the total mass of the activated carbon capture agent, the temperature of the high-temperature hot air flow is 190°C, and the particle size of the microcapsule particles is 115μm.
[0134] In step 4, the mass of the remaining activated carbon capture agent is 52wt% of the total mass of the activated carbon capture agent; the stirring temperature of the mechanical stirrer is room temperature, the stirring speed is 165rpm, and the stirring time is 4.5min.
[0135] In step 5, the mixing temperature of the mixing pot is room temperature, the mixing speed is 55 rpm, and the mixing time is 70 s.
[0136] In step six, the mixing temperature of the mixing pot is room temperature, the mixing speed is 55 rpm, and the mixing time is 3.2 min.
[0137] In step seven, the mixing temperature of manual mixing is room temperature and the mixing time is 1.8 min; the inner cavity of the specimen molding mold has a length of 100 mm, a width of 100 mm, and a height of 100 mm; and the mass of the partial microcapsule particles is 28 wt% of the total mass of the microcapsule particles.
[0138] In step eight, the standing temperature is room temperature, the standing time is 24 hours, and the curing time is 28 days.
[0139] In step nine, the mass of the remaining microcapsule particles is 72wt% of the total mass of the microcapsule particles, and the mass of the anhydrous ethanol is 28 times the mass of the remaining microcapsule particles.
[0140] Embodiment five:
[0141] According to another preferred embodiment of the enhanced recycled aggregate cement concrete and preparation method based on long-term carbon sequestration of the present invention, its material ratio, preparation process, technical principle, equipment used, beneficial effects, etc. are basically the same as those of the first embodiment, except that:
[0142] The added amounts of various substances in the enhanced recycled aggregate cement concrete are as follows: 48wt% of recycled aggregate component, 2.5wt% of activated carbon capture agent, 1.5wt% of microencapsulated material, 24wt% of river sand, 1.2wt% of water reducer, 15wt% of cement, 1.8wt% of auxiliary admixture and 6wt% of water, as percentage by mass of the enhanced recycled aggregate cement concrete.
[0143] The mass percentage of each substance added in the recycled aggregate component is 40wt% of aggregate and 60wt% of recycled aggregate; the aggregate is limestone, and the recycled aggregate is low-brick-concrete construction waste recycled aggregate, that is, construction waste generated by the demolition of concrete buildings, and its brick-concrete content is 5-10wt%. The aggregate includes four particle sizes, and the mass percentage of each particle size in the aggregate is 11wt% for particle size greater than or equal to 19mm, 40wt% for particle size 16-19mm, 45wt% for particle size 9.5-16mm, and 4wt% for particle size 4.75-9.5mm; the recycled aggregate includes four particle sizes, and the mass percentage of each particle size in the recycled aggregate is 11wt% for particle size greater than or equal to 19mm, 40wt% for particle size 16-19mm, 45wt% for particle size 9.5-16mm, and 4wt% for particle size 4.75-9.5mm.
[0144] The added amount of each substance in the activated carbon capture agent accounts for the mass percentage of the activated carbon capture agent, which is 43wt% of modified magnesium oxide, 30wt% of calcium hydroxide component, 12wt% of silicate, 6wt% of catalyst, 6wt% of industrial solid waste, and 3wt% of trace enhancer. The added amount of each substance in the calcium hydroxide component accounts for the mass percentage of the calcium hydroxide component, which is 96wt% of calcium hydroxide, 2.5wt% of metal oxide, and 1.5wt% of rare earth element. The metal oxide is Al2O3, the rare earth element is Ce, and the particle size of the calcium hydroxide, the metal oxide, and the rare earth element is 0.4μm. The silicate is anhydrous sodium silicate, the catalyst is magnesium aluminum layered double hydroxide, the industrial solid waste is steel slag, the trace enhancer is a manganese-based compound, and the manganese-based compound is potassium manganate.
[0145] The mass percentage of each substance added in the microencapsulation material is chitosan 20wt%, polylactic acid 56wt%, and silica microspheres 24wt%, and the ratio of the mass of the chitosan to the mass of the polylactic acid is 1:2.8, ensuring that it is within the range of 1:2.2-3, and the particle size of the silica microspheres is 4μm.
[0146] The river sand includes eight particle sizes, and the mass percentage of each particle size is as follows: 8wt% of the particle size is 4.75-9.5mm, 4wt% of the particle size is 2.36-4.75mm, 15wt% of the particle size is 1.18-2.36mm, 18wt% of the particle size is 0.6-1.18mm, 25wt% of the particle size is 0.3-0.6mm, 22wt% of the particle size is 0.15-0.3mm, 4wt% of the particle size is 0.075-0.15mm, and 4wt% of the particle size is 0-0.075mm. The water reducer is a high-performance polycarboxylate water reducer, the cement is PO 42.5 ordinary Portland cement, and the auxiliary admixture is fly ash.
[0147] In step 1, during the preparation of the recycled aggregate component: the recycled aggregates of each particle size are soaked in a sodium carbonate solution with a concentration of 5%, and the sodium carbonate solution is sufficient to cover the recycled aggregates of each particle size. The soaking temperature is room temperature and the soaking time is 1.2 hours. After the soaking is completed, melamine is added to the sodium carbonate solution and the recycled aggregates of each particle size and stirred. The amount of melamine added is 0.6wt% of the total mass of the recycled aggregate. The stirring temperature is room temperature and the stirring time is 0.6h. After the stirring is completed, the carbonization pretreatment of the recycled aggregate is completed.
[0148] In the preparation process of the activated carbon capture agent: firstly, modified magnesium oxide is prepared, that is, magnesium oxide is placed in a calcining furnace for low-temperature calcination, the calcination temperature is 750°C, and the calcination time is 4.5h, the calcined magnesium oxide is washed and purified, and the washed and purified magnesium oxide is placed in an oven for drying treatment, the drying temperature is 85°C, and the drying time is 2.2h, and alkaline carbonate is added to the dried magnesium oxide and mixed evenly to obtain modified magnesium oxide, the addition amount of alkaline carbonate is 1.5wt% of the mass of the modified magnesium oxide, and the alkaline carbonate is lithium carbonate; finally, the solid powder is placed in an oven for drying treatment, the drying temperature is 85°C, and the drying time is 2.2h. After the drying treatment is completed, the activated carbon capture agent can be obtained.
[0149] In the preparation process of the microencapsulation material: chitosan and polylactic acid are mixed evenly and then put into anhydrous ethanol to dissolve to form a solution, and the mass of the anhydrous ethanol is 22 times the total mass of the chitosan and polylactic acid.
[0150] In step three, the mass of the part of the activated carbon capture agent is 42wt% of the total mass of the activated carbon capture agent, the temperature of the high-temperature hot air flow is 170°C, and the particle size of the microcapsule particles is 105μm.
[0151] In step 4, the mass of the remaining part of the activated carbon capture agent is 58wt% of the total mass of the activated carbon capture agent; the stirring temperature of the mechanical stirrer is room temperature, the stirring speed is 135rpm, and the stirring time is 5.5min.
[0152] In step 5, the mixing temperature of the mixing pot is room temperature, the mixing speed is 45 rpm, and the mixing time is 80 s.
[0153] In step six, the mixing temperature of the mixing pot is room temperature, the mixing speed is 45 rpm, and the mixing time is 3.8 min.
[0154] In step seven, the mixing temperature of manual mixing is room temperature and the mixing time is 1.2 min; the inner cavity of the specimen molding mold has a length of 100 mm, a width of 100 mm, and a height of 100 mm; and the mass of the partial microcapsule particles is 22 wt% of the total mass of the microcapsule particles.
[0155] In step eight, the standing temperature is room temperature, the standing time is 24 hours, and the curing time is 28 days.
[0156] In step nine, the mass of the remaining microcapsule particles is 78wt% of the total mass of the microcapsule particles, and the mass of the anhydrous ethanol is 22 times the mass of the remaining microcapsule particles.
[0157] Comparative Example 1:
[0158] This comparative example is a natural aggregate cement concrete, which is composed of aggregate, river sand, water reducer, cement, auxiliary admixture and water, without adding recycled aggregate, activated carbon capture agent and microencapsulation material. The mass percentage of each substance in the natural aggregate cement concrete is 45-50wt% of aggregate, 24-28wt% of river sand, 0.8-1.2wt% of water reducer, 15-18wt% of cement, 1.2-4.8wt% of auxiliary admixture and 6-9wt% of water. The specific substances selected, the gradation of aggregate and the gradation of river sand are the same as those in Example 1; the preparation process and process parameters of the natural aggregate cement concrete are also basically the same as those in Example 1, wherein the preparation steps of the recycled aggregate component, the activated carbon capture agent and the microencapsulation material are deleted.
[0159] Comparative Example 2:
[0160] This comparative example is ordinary recycled aggregate cement concrete, which is composed of recycled aggregate components, river sand, water reducer, cement, auxiliary admixtures and water, without adding activated carbon capture agent and microencapsulation material. The mass percentage of each substance in the ordinary recycled aggregate cement concrete is 45-50wt% of recycled aggregate components, 24-28wt% of river sand, 0.8-1.2wt% of water reducer, 15-18wt% of cement, 1.2-4.8wt% of auxiliary admixtures, and 6-9wt% of water; the mass percentage of each substance in the recycled aggregate component is 40-60wt% of aggregate and 40-60wt% of recycled aggregate. The specific substances selected, the gradation of recycled aggregate, the gradation of aggregate, the gradation of river sand, etc. are the same as those in Example 1; the preparation process and process parameters of ordinary recycled aggregate cement concrete are also basically the same as those in Example 1, wherein the preparation steps of activated carbon capture agent and microencapsulation material are deleted.
[0161] The above five embodiments and two comparative examples were subjected to compressive strength test, splitting tensile strength test, elastic modulus test, SEM test and XRD test, and the test equipment, test environment, test conditions, sample shape and size used were all the same.
[0162] After 28 days of standard curing, the specimens were subjected to compressive strength test, splitting tensile strength test, and elastic modulus test. The test temperatures of the three tests were all room temperature, the speed of the compressive strength test was 0.6 MPa / s, the speed of the splitting tensile strength test was 0.06 MPa / s, and the speed of the elastic modulus test was 0.5 MPa / s. Three sets of parallel tests were performed on each embodiment and comparative example, and the average value was finally taken. The average value of the test results is shown in Table 1.
[0163] Table 1 Test results of compressive strength, splitting tensile strength and elastic modulus (average values)
[0164]
[0165] From the test results in Table 1, it can be seen that the compressive strength, splitting tensile strength and elastic modulus of the long-term carbon sequestration enhanced recycled aggregate cement concrete of the five embodiments are close to those of the natural aggregate cement concrete of Comparative Example 1, and compared with the ordinary recycled aggregate cement concrete of Comparative Example 2, the compressive strength is at least increased by 17.98%, the splitting tensile strength is at least increased by 41.78%, and the elastic modulus is at least increased by 25.25%. After long-term carbon sequestration, the long-term carbon sequestration enhanced recycled aggregate cement concrete of the five embodiments improves the strength of cement concrete, that is, it makes full use of recycled aggregates and ensures that its mechanical properties are close to those of natural aggregate cement concrete.
[0166] After 28 days of standard curing and 6 months of outdoor exposure, the specimens were subjected to SEM and XRD tests, respectively. Figure 5These are SEM photos of the long-term carbon sequestration enhanced recycled aggregate cement concrete specimens of Example 1 after 28 days of standard curing and 6 months of outdoor exposure, where: (a) is 28 days of standard curing, and (b) is 6 months of outdoor exposure; Figure 6 These are SEM photos of the ordinary recycled aggregate cement concrete specimens of Comparative Example 2 after standard curing for 28 days and outdoor exposure for 6 months, where: (a) is standard curing for 28 days, and (b) is outdoor exposure for 6 months.
[0167] from Figure 5 and Figure 6 It can be seen that in the ordinary recycled aggregate cement concrete of Comparative Example 2, the interface transition zone is relatively fragile. As time goes by, the mechanical fracture section increases, the carbonization process is slow, the filling of calcium sulfonate in the cracks is limited, and there are incompletely hydrated Ca(OH)2 and hydrated calcium silicate CSH. In contrast, although the long-term carbon sequestration enhanced recycled aggregate cement concrete of Example 1 also has cracks, thanks to the improvement of carbon capture capacity, CO2 penetration promotes the reaction of cement components with recycled aggregates to generate calcium carbonate, which can effectively repair pores and cracks; after 6 months of outdoor exposure, carbonization continues, and CSH becomes the dominant reactant, which is converted into cubic calcium carbonate and fine needle-shaped calcium sulfonate, further filling the interface cracks. As the carbonization reactants decrease, the carbon sequestration capacity gradually approaches saturation; this process demonstrates the self-repair and carbon fixation mechanism of the long-term carbon sequestration enhanced recycled aggregate cement concrete under carbonization.
[0168] Figure 7 XRD images of the long-term carbon sequestration enhanced recycled aggregate cement concrete specimen of Example 1 after 28 days of standard curing and 6 months of outdoor exposure, where: (a) is 28 days of standard curing, and (b) is 6 months of outdoor exposure; Figure 8 The XRD photos of the ordinary recycled aggregate cement concrete specimens in comparative example 2 after 28 days of standard curing and 6 months of outdoor exposure, where (a) is 28 days of standard curing and (b) is 6 months of outdoor exposure. The vertical axis in the figure is the diffraction intensity, which is proportional to the substance content. Figure 7 and Figure 8 It can be seen that with the extension of outdoor exposure time, the CaCO3 content in the ordinary recycled aggregate cement concrete of Comparative Example 2 increases gradually; in comparison, the CaCO3 content of the long-term carbon sequestration enhanced recycled aggregate cement concrete of Example 1 is higher in the same stage, which indicates that it has good carbon capture and carbon sequestration capabilities. After 6 months of outdoor exposure, the proportion of CaCO3 continues to increase, which shows that it has long-term carbon sequestration capabilities.
[0169] In the above embodiments and comparative examples, the raw materials such as aggregate, cement, auxiliary admixture, river sand, water reducer, etc. were purchased from Beijing Municipal Road and Bridge Building Materials Group Co., Ltd.; the recycled aggregate was purchased from Beijing Urban Green Source Environmental Protection Technology Co., Ltd., which mainly came from the construction waste generated by the demolition of concrete buildings within 30 kilometers of the disposal site. The construction waste was crushed in the treatment plant to obtain low-brick-concrete construction waste recycled aggregate; the raw materials used for preparing activated carbon capture agent and microencapsulation material were purchased from Aladdin Reagent Co., Ltd.
[0170] Special note: The technical solution of the present invention involves many parameters, and the synergistic effects between the various parameters need to be comprehensively considered to obtain the beneficial effects and significant progress of the present invention. Moreover, the value ranges of the various parameters in the technical solution are obtained after a large number of experiments. For each parameter and the combination of each parameter, the inventor has recorded a large amount of experimental data. Due to space limitations, the specific experimental data will not be disclosed here.
[0171] It is not difficult for those skilled in the art to understand that the enhanced recycled aggregate cement concrete based on long-term carbon sequestration and the preparation method of the present invention include any combination of the invention content and the specific implementation method of the above-mentioned invention specification and the various parts shown in the drawings. Due to the limited space and to make the specification concise, the various schemes composed of these combinations are not described one by one. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An enhanced recycled aggregate cement concrete based on long-term carbon sequestration, characterized in that: The added amounts of various substances in the enhanced recycled aggregate cement concrete are as follows: 45-50wt% of recycled aggregate components, 2-5wt% of activated carbon capture agent, 1-2wt% of microencapsulated material, 24-28wt% of river sand, 0.8-1.2wt% of water reducer, 15-18wt% of cement, 1.2-4.8wt% of auxiliary admixtures, and 6-9wt% of water, as a percentage of the mass of the enhanced recycled aggregate cement concrete.
2. The enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 1, characterized in that: The added amount of each substance in the recycled aggregate component accounts for 40-60wt% of the mass percentage of the recycled aggregate component, and the recycled aggregate is 40-60wt%; the aggregate includes any one or more of limestone, basalt, granite, and diabase; the recycled aggregate is low-brick-concrete construction waste recycled aggregate, that is, construction waste generated by the demolition of concrete buildings, and its brick-concrete content is 5-10wt%.
3. The enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 2, characterized in that: The aggregate includes four particle sizes, and the mass percentage of each particle size is as follows: particle size greater than or equal to 19 mm accounts for 8-11wt%, particle size 16-19 mm accounts for 34-50wt%, particle size 9.5-16 mm accounts for 35-51wt%, and particle size 4.75-9.5 mm accounts for 4-6wt%; the recycled aggregate includes four particle sizes, and the mass percentage of each particle size is as follows: particle size greater than or equal to 19 mm accounts for 8-11wt%, particle size 16-19 mm accounts for 34-50wt%, particle size 9.5-16 mm accounts for 35-51wt%, and particle size 4.75-9.5 mm accounts for 4-6wt%.
4. The enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 3, characterized in that: The added amounts of various substances in the activated carbon capture agent are as follows: 40-50wt% of modified magnesium oxide, 20-30wt% of calcium hydroxide component, 10-20wt% of silicate, 5-10wt% of catalyst, 5-10wt% of industrial solid waste, and 1-3wt% of trace enhancer, based on the mass percentage of the activated carbon capture agent.
5. The enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 4, characterized in that: The added amount of each substance in the calcium hydroxide component accounts for the mass percentage of the calcium hydroxide component, calcium hydroxide 95-98.5wt%, metal oxide 1-3wt%, rare earth element 0.5-2wt%, the metal oxide is Al2O3 and / or Fe2O3, the rare earth element is Ce and / or La, and the particle size of the calcium hydroxide, the metal oxide, and the rare earth element is 0.1-1μm; The silicate includes any one or more of anhydrous sodium silicate, potassium silicate, sodium potassium silicate, and sodium potassium composite silicate; the catalyst includes any one or more of titanium oxide, zirconium dioxide, magnesium aluminum layered double hydroxide, and hydrated magnesium aluminate carbonate; the industrial solid waste includes any one or more of steel slag, carbide slag, fly ash, desulfurized gypsum, red mud, and glass slag; the trace enhancer is a lithium-based compound and / or a manganese-based compound, the lithium-based compound includes any one or more of lithium carbonate, lithium hydroxide, and lithium chloride, and the manganese-based compound includes any one or more of manganese dioxide, manganese chloride, and potassium manganate.
6. The enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 5, characterized in that: The mass percentage of each substance added in the microencapsulation material is chitosan 20-30wt%, polylactic acid 50-60wt%, and silica microspheres 20-30wt%, and the ratio of the mass of the chitosan to the mass of the polylactic acid is 1:2.2-3, and the particle size of the silica microspheres is 0.01-10μm.
7. The enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 6, characterized in that: The river sand includes eight particle sizes, and the mass percentage of each particle size of the river sand is: 4.75-9.5mm accounts for 7-9wt%, 2.36-4.75mm accounts for 3-5wt%, 1.18-2.36mm accounts for 10-16wt%, 0.6-1.18mm accounts for 15-25wt%, 0.3-0.6mm accounts for 25-35wt%, 0.15-0.3mm accounts for 20-30wt%, 0.075-0.15mm accounts for 4-6wt%, and 0-0.075mm accounts for 4-6wt%.
8. The enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 7, characterized in that: The water reducer is a high-performance polycarboxylate water reducer, the cement is PO 42.5 ordinary Portland cement, and the auxiliary admixtures include any one or more of fly ash, slag powder, and silica fume.
9. A method for preparing enhanced recycled aggregate cement concrete based on long-term carbon sequestration, characterized in that: The method for preparing the enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to any one of claims 1 to 8 comprises the following steps in chronological order: Step 1: prepare recycled aggregate components, activated carbon capture agent, and microencapsulation material respectively according to the designed material ratio and process parameters; Step 2: Weigh the recycled aggregate components, activated carbon capture agent, microencapsulated material, river sand of various particle sizes, water reducer, cement, auxiliary admixtures and water according to the designed material ratio; Step 3: adding part of the activated carbon capture agent to the microencapsulation material and stirring evenly, so that the activated carbon capture agent is wrapped inside the microencapsulation material to form a microcapsule raw material liquid; using a spray drying method to disperse the microcapsule raw material liquid into fine droplets, and quickly evaporate the solvent in a high-temperature hot air flow, so that the solid matter in the microcapsule raw material liquid is polymerized and solidified to form microcapsule particles; Step 4: Put the recycled aggregate component and the remaining part of the activated carbon capture agent into a mechanical mixer for stirring. After stirring evenly, take out the mixture of the recycled aggregate component and the activated carbon capture agent from the mechanical mixer for standby use; Step 5: sequentially put river sand of each particle size, cement, a mixture of recycled aggregate components and an activated carbon capture agent, and auxiliary admixtures into a mixing pot for mixing, and set aside after mixing evenly; Step 6: Put water and a water reducing agent into a container and mix them evenly to form a mixed solution of water and the water reducing agent; put the mixed solution of water and the water reducing agent into a mixing pot and mix it together with the materials in the mixing pot, and after mixing evenly, obtain an enhanced recycled aggregate cement concrete slurry based on carbon sequestration; Step 7: taking the obtained carbon sequestration-based enhanced recycled aggregate cement concrete slurry out of the mixing pot and placing it into a storage container while performing manual mixing; After the manual mixing is completed, the carbon sequestration-based enhanced recycled aggregate cement concrete slurry is filled into the specimen forming mold, and the upper surface of the slurry in the specimen forming mold is scraped flat with a scraper, and then part of the microcapsule particles are evenly spread on the upper surface of the slurry, and the upper surface of the microcapsule particles is scraped flat with a scraper; Step 8: Place the specimen molding mold on an electric vibration table, start the electric vibration table, and start vibration molding. During the vibration molding process, if a depression occurs, add the carbon-sequestered enhanced recycled aggregate cement concrete slurry to the depressed part; after the vibration molding is completed, let the specimen molding mold and the formed slurry inside it stand for a certain period of time before demolding, and then put it into a standard curing room for curing to obtain a carbon-sequestered enhanced recycled aggregate cement concrete specimen; Step nine: dissolve the remaining microcapsule particles in anhydrous ethanol to form a suspension; stir the suspension evenly and evenly coat the suspension on the outer surface of the enhanced recycled aggregate cement concrete specimen based on carbon sequestration to obtain an enhanced recycled aggregate cement concrete specimen based on long-term carbon sequestration.
10. The method for preparing enhanced recycled aggregate cement concrete based on long-term carbon sequestration according to claim 9, characterized in that: In step 1, the preparation process of the recycled aggregate component is as follows: first, the construction waste generated by the demolition of concrete buildings is crushed and cleaned, and sieved according to the designed particle size grades to obtain recycled aggregates of various particle sizes; then, the recycled aggregates of various particle sizes are weighed according to the designed material ratio, and carbonization pretreatment is performed, that is, the recycled aggregates of various particle sizes are soaked in a sodium carbonate solution with a concentration of 5%, and the sodium carbonate solution is sufficient to cover the recycled aggregates of various particle sizes, and the soaking temperature is room temperature and the soaking time is 1- 2h, after the soaking is completed, melamine is added to the sodium carbonate solution and the recycled aggregates of each particle size and stirred, the amount of melamine added is 0.5-1wt% of the total mass of the recycled aggregate, the stirring temperature is room temperature, and the stirring time is 0.5-1h. After the stirring is completed, the carbonization pretreatment of the recycled aggregate is completed; finally, according to the designed material ratio, the aggregates of each particle size are weighed, and the aggregates of each particle size and the recycled aggregates of each particle size after carbonization pretreatment are evenly mixed to obtain the recycled aggregate component; In step 1, the preparation process of the activated carbon capture agent is to first prepare modified magnesium oxide, that is, put the magnesium oxide into a calcining furnace for low-temperature calcination, the calcination temperature is 700-900°C, the calcination time is 3-5h, the calcined magnesium oxide is washed and purified, and the washed and purified magnesium oxide is placed in an oven for drying, the drying temperature is 80-100°C, and the drying time is 2-3h. Alkaline carbonate is added to the dried magnesium oxide and mixed evenly to obtain modified magnesium oxide, the addition amount of the alkaline carbonate is 1-3wt% of the mass of the modified magnesium oxide, and the alkaline carbonate includes lithium carbonate, potassium carbonate, and carbonate. Any one or more of cesium; secondly, prepare the calcium hydroxide component, that is, mix the calcium hydroxide, metal oxides and rare earth elements at room temperature according to the designed material ratio; then, according to the designed material ratio, mix the modified magnesium oxide, calcium hydroxide component, silicate, catalyst, industrial solid waste and trace enhancer at room temperature, and ball mill the mixed materials to obtain a solid powder with a particle size of less than 5μm; finally, put the solid powder into an oven for drying at a drying temperature of 80-100°C and a drying time of 2-3h. After the drying process is completed, an activated carbon capture agent can be obtained; In step 1, the preparation process of the microencapsulated material is as follows: first, chitosan, polylactic acid, and silica microspheres are weighed according to the designed material ratio for use; then, the chitosan and polylactic acid are mixed evenly and then dissolved in anhydrous ethanol to form a solution, wherein the mass of the anhydrous ethanol is 20-30 times the total mass of the chitosan and polylactic acid; finally, the silica microspheres are added to the solution and stirred evenly to obtain the microencapsulated material; In step 3, the mass of the part of the activated carbon capture agent is 40-50wt% of the total mass of the activated carbon capture agent, the temperature of the high-temperature hot air flow is 150-200° C., and the particle size of the microcapsule particles is 100-120 μm; In step 4, the mass of the remaining activated carbon capture agent is 50-60wt% of the total mass of the activated carbon capture agent; the stirring temperature of the mechanical stirrer is room temperature, the stirring speed is 120-180rpm, and the stirring time is 4-6min; In step 5, the mixing temperature of the mixing pot is room temperature, the mixing speed is 40-60 rpm, and the mixing time is 60-90 s; In step 6, the mixing temperature of the mixing pot is room temperature, the mixing speed is 40-60 rpm, and the mixing time is 3-4 min; In step 7, the mixing temperature of the manual mixing is room temperature, and the mixing time is 1-2 minutes; the length of the inner cavity of the specimen molding mold is 100 mm, the width is 100 mm, and the height is 100 mm; the mass of the part of the microcapsule particles is 20-30wt% of the total mass of the microcapsule particles; In step eight, the standing temperature is room temperature, the standing time is 24 hours, and the curing time is 28 days; In step nine, the mass of the remaining microcapsule particles is 70-80wt% of the total mass of the microcapsule particles, and the mass of the anhydrous ethanol is 20-30 times the mass of the remaining microcapsule particles.
Citation Information
Patent Citations
Carbon sequestration all-solid-waste fabricated permeable pavement system
CN117536045A
Rocks and aggregate, and methods of making and using the same
CA2670049A1
Method for efficiently trapping carbon dioxide in flue gas
CN114259837A
Exhaust system for lean burn ic engine including particulate filter and NOx absorbent
CN1784540A
Process for the Production of Metal Oxides
US20210261427A1
Cited By
Cement-based interface reinforcing agent for brick-concrete recycled aggregate and preparation method of cement-based interface reinforcing agent
CN120554015A